EVALUASI PELAPORAN KEUANGAN TAHUN 2016-2018 DENGAN MODEL CIPP (CONTEXT, INPUT, PROCESS, PRODUCT) PADA PUSAT PENELITIAN KEBIJAKAN PENDIDIKAN DAN KEBUDAYAAN - A Rina Herawati; Hasti Kusumawati (Dialogue : Jurnal Ilmu Administrasi Publik, 2020)
This research aims to investigate the quality implementation of financial reporting in Research Centre for Educational and Cultural Policies, Research and Development Agency, Ministry of Education and Culture, using CIPP (Context, Input, Process, Product) evaluation model. Focus of the problem researched is how to evaluate the financial reporting in Research Centre for Educational and Cultural Policies, Research and Development Agency, Ministry of Education and Culture. The descriptive methodology was used with qualitative approach. Data collection techniques were interview and document review. Research results are as follows: (1) Context Aspect is conformity between purpose and target in financial reporting in Centre for Policy Research with Government Regulation No. 71 Year 2010 concerning Standard for Government Accounting for the interests of accountability, management, transparency, and performance evaluation; (2) Input Aspect is resource in financial reporting, including human resource and facilities and infrastructure (computer, internet network, and office facilities) which have been adequate to support timely financial reporting; (3) Process Aspect is in the process of financial reporting implementation in which the problems found are late BMN reporting, BMN recording which is not orderly administration, the lack of coordination and communication among planner, executor, and application operator, the role of leader which is is still inadequate, and SPI supervision which is not yet optimal; and (4) Product Aspect is financial statement in Research Centre for Educational and Cultural Policies which is relevant, reliable, and useful as source of information in management decision. Suggestions to be given are as follows: (1) Periodic coordination between stakeholders; (2) Intensive evaluation of employee performance in the process of financial reporting; (3) Suggesting SPI task as a supervisor in internal control as functional position; and (4) Recruiting more employees as administrator and operator in BMN application